The ultimate negotiation book : discover what top negotiators do, master persuasion and influence, build rapport with NLP /: discover what top negotiators do, master persuasion and influence, build rapport with NLP. (2018) - Fleming, Peter Ronald; Shapiro, Mo; McLanachan, Di
No abstract available